MAXIMUM ECONOMIC YIELD PERIKANAN TANGKAP (Studi Manajemen Perikanan Tangkap di WPPNRI 711) - Djamarel Hermanto (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2018)
This research aims to calculate small pelagic optimum exploitation in economic term based on the sustainable use of fisheries. The research conducted in Regional Fisheries Management Republic of Indonesia (WPPNRI) 711 is rich small pelagic and is a fertile area activities of legal and illegal fishing, using primary data and secondary data. Primary data were collected from interviews with local fishermen and marine superintendent using interview technique. While secondary data obtained from the Ministry of Maritime Affairs and Fisheries (MMAF) Republic of Indonesia, the Indonesian Fleet Command Office of the Western Region and the Office of Maritime Security Agency of Indonesia. Data series of 2005 to 2015 were also analyzed. Bioeconomic analysis using a model for the analysis of Gordon Schaefer and economic benefits using surplus production model developed by Fox in this study. Optimum economic exploitation of small pelagic fishery management in WPPNRI 711 is 4759 fishing ships effort, 15,318.92 tons per year productions and IDR 264,028.60 billion economic rent per year. Exploitation rate carried out by fishermen either viewed from the business as well as the catch landed indicates the condition is still below the optimum level so that they can be developed with due regard to the principles of prudence in fisheries economic management of the Small Pelagic.